Reexamining X‐mode suppression and fine structure in artificial E region field‐aligned plasma density irregularities. Issue 5 (5th September 2013) - Miceli, R. J.; Hysell, D. L.; Munk, J.; McCarrick, M.; Huba, J. D.
<x xml:space="preserve">Abstract</x> [1] Artificial field‐aligned plasma density irregularities (FAIs) were generated in the E region of the ionosphere above the High Frequency Active Auroral Research Program facility during campaigns in May and August of 2012 and observed using a 30 MHz coherent scatter radar imager in Homer, Alaska. The purpose of this ionospheric modification experiment was to measure the threshold pump power required to excite thermal parametric instabilities by O‐mode heating and to investigate the suppression of the FAIs by simultaneous X‐mode heating. We find that the threshold pump power for irregularity excitation was consistent with theoretical predictions and increased by approximately a factor of 2 when X‐mode heating was present. A modified version of the Another Model of the Ionosphere (SAMI2) ionospheric model was used to simulate the threshold experiments and suggested that the increase was entirely due to enhanced D region absorption associated with X‐mode heating. Additionally, a remarkable degree of fine structure possibly caused by natural gradient drift instability in the heater‐modified volume was observed in experiments performed during geomagnetically active conditions.